DIPLOMASI PALESTINA MENJADI NEGARA PENGAMAT NON- ANGGOTA DI PERSERIKATAN BANGSA-BANGSA (PBB) TAHUN 2011-2012 - Badri Alzaky; Faisyal Rani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research aimed to describe how Palestine movement to get independence and recognition from all above United Nations member state. In this research will explain the progess of Palestine‟s Authority to become non-member observer state in United Nations. Authority of Palestine was the Palestine‟s people representation that had right to vote and right to submit point of view at international forum. Palestine Liberazation Organization (PLO) take important role for Palestine movement. In any relations, especially foreign relations, Palestine had some of good attitude. But all of Palestine disputes with Israel hamper the independence of Palestine.Researcher analyzed this case using qualitative methods to find data and facts through some literature. The literature collected from books, journals, mass media and websites. Researcher use realism perspective. The level analysis of the research is nation-state and also use international cooperation theory by K.J. Holsti.From this research it can be seen, Palestine used some steps toward international rezime. There are three steps that will shown in this research. First, by using confference diplomacy, under Mahmoud Abbas rezime as President of Palestine‟s Authority used diplomatic relations with other nation state with delivery speech in front of the forum. Second steps with parlementary diplomacy made Palestine as a non-member observer state in United Nations after 67th general assembly at 44th panel discussion on November 29th, 2012. This result supported by 138 countries, rejected by 9 countries, 41 counstries abstain, and 5 countries absen. The last step from Palestine movement for recognition by using international organization. This seen when Palestine joined as a full membership of UNESCO. Also use of „state of Palestine” in any diplomatic relations and international organization.Keywords: Palestine, PLO, Confference Diplomacy, Parlementary Diplomacy, United Nations, Non Member Observer State